The effects of deposition potential on the optical, morphological and mechanical properties of DLC films produced by electrochemical deposition technique at low voltages - Aslan, Naim; Basman, Necati; Uzun, Orhan; Erkovan, Mustafa; Yakuphanoğlu, Fahrettin (Paradigm Publishing Services-de Gruyter Brill Sp Zoo, 2019)
Diamond-like carbon (DLC) films were electrochemically deposited onto indium tin oxide (ITO) substrates using acetic acid and deionized water as electrolyte at low deposition voltages (2.4 V and 60 V). The transmittance of the films was investigated by UV spectrometry. Transmittance measurements versus wavelength revealed that the films transmit 86 % to 89 % light in visible region and band gap of the films varies between 3.87 eV and 3.89 eV. Atomic force microscopy (AFM) and scanning electron microscopy (SEM) were used for structural characterization to evaluate surface morphology of the DLC films. The grain size and the surface roughness increased for the films prepared at higher deposition potential, while their measured average height decreased. The mechanical properties (hardness H and elastic modulus E-r) were determined from load-displacement curves which were obtained by using nanoindentation method. Hardness and elastic modulus of the films increased as the deposition voltage of the films increased from 2.4 V to 60 V.
Keywords: DLC films; optical properties; morphological properties; mechanical characterization